Measuring the cell-free layer in circular microchannels - Fidalgo, Cátia (2011)
One of the most interesting hemodynamic phenomenon observed both in vivo and in vitro studies is known as Fahraeus-Lindqvist effect, in which the apparent blood viscosity decreases as the tube diameter is reduced, for narrow tubes (< 300 μm). The physical reason behind this phenomenon is the creation of a marginal cell-free layer at regions adjacent to the tube wall. Although intensively studied, the complex formation of the cell-free layer has not yet been convincingly described mainly due to multi-physical and hemorheological factors that affect this phenomenon. The main purpose of this experimental work is to study the effect of the hematocrit (Hct) and temperature on the thickness of the cell-free layer in both glass capillaries and circular polydimethylsiloxane (PDMS) microchannels using an optical technique. The internal diameter of the glass and PDMS microchannels are 100 m and 73±2 m, respectively. The microchannels were placed on the stage of the inverted microscope and the temperature of the stage was adjusted by means of a thermo plate controller. The flow rate of the working fluids was controlled using a syringe pump. The images were recorded using a confocal microscopy system and transferred to the computer to be evaluated in Image J (NIH) using different plug-ins (MTrackJ and FeatureJ). The recorded images show a clear formation of a cell-free layer of variable thickness depending on experimental conditions.